The role of intra-articular administration of Fetuin-A in post-traumatic knee osteoarthritis: an experimental study in a rat model - Eleni Pappa; Savvas Papadopoulos; Laskarina-Maria Korou; Despina N. Perrea; Spiridon Pneumaticos; Vasileios S. Nikolaou (Journal of Experimental Orthopaedics, 2019)
Abstract  Background The purpose of this study is to investigate the possible attenuating role of the intra-articular administration of Fetuin-A in post-traumatic secondary osteoarthritis in rats, and also its effect on the systematic levels of interleukins (ILs)-2,4,7, bone morphogenetic proteins (BMPs) 2, 4, 7, C-Reactive Protein (CRP) and Fetuin-A. Methods Thirty male Sprague Dawley rats were separated in two groups where post-traumatic osteoarthritis was induced surgically by Anterior Cruciate Ligament Transection and the transection of the Medial Collateral Ligament of the right knee. In the Control Group, only the surgical intervention took place. In Fetuin Group, along with the induction of osteoarthritis, a single dose of bovine fetuin was administrated intra-articularly, intra-operatively. Both groups were examined for 8 weeks. The levels of interleukins, bone morphogenetic proteins, Fetuin-A and C-Reactive Protein were evaluated by ELISA of peripheral blood in three time periods: preoperatively, 5 and 8 weeks post-operatively. Osteoarthritic lesions of the knee were classified according to the Osteoarthritis Research Society International Grading System and the Modified Mankin Score, by histologic examination. Results IL-2 levels were significantly decreased in the Fetuin Group. No statistical difference was signed on the levels of IL-7, BMP-2,4,7 and Fetuin-A between the two groups. CRP levels were significantly increased in the Fetuin Group in 5 weeks of the experiment. Fetuin Group signed better scores according to the OARSI classification system and Modified Mankin Score, without any statistical significance. Conclusions Intra-articular administration of Fetuin-A restrictively affected the progression of post-traumatic arthritis in rats, as only the levels of IL-2 were decreased as well as limited osteoarthritic lesions were observed on the Fetuin Group.